Experimental and numerical investigation on spray cooling of radiator in fuel cell vehicle - Chu-Qi Su (Energy Reports, 2022)
In view of the heat transfer problem in fuel cell vehicle at climbing and high temperature environment, a method for spray cooling of the radiator using water produced by fuel cell is proposed. In order to evaluate the effectiveness of this method and predict the best working condition of spray at climbing and high temperature environment, a test bench was built to investigate the effects of four spray temperatures of 48 °C, 58 °C, 68 °C, and 74 °C on the cooling performance of the radiator. A three-dimensional model of the radiator was established, and the numerical simulation of radiator spray cooling was carried out based on the Euler–Lagrangian approach, and the validity and accuracy of the numerical simulation was verified by the experiments. Then the different spray angles and spray flow rates were considered to study the convective heat transfer coefficient of the radiator’s air side at climbing and high temperature environment, and the optimal working parameters were obtained. The results indicated that the spray at 74 °C still had a significant cooling performance on the radiator with the evaporation of the liquid film. The initial state of the spray hitting the surface of the radiator can be simulated, and the cooling performance can be evaluated by comparing the convective heat transfer coefficient of the air side of the radiator. The inclined spray is more effective than the vertical spray. At the interference of external wind speed of 40 km/h, the best heat transfer coefficient can be obtained with the 55° spray angle and the 9.44 g/s spray flow rate. This numerical simulation process can provide a reference for the design of fuel cell vehicle spray cooling system.